2016
DOI: 10.1093/nar/gkw1114
|View full text |Cite
|
Sign up to set email alerts
|

Different enhancer classes in Drosophila bind distinct architectural proteins and mediate unique chromatin interactions and 3D architecture

Abstract: Eukaryotic gene expression is regulated by enhancer–promoter interactions but the molecular mechanisms that govern specificity have remained elusive. Genome-wide studies utilizing STARR-seq identified two enhancer classes in Drosophila that interact with different core promoters: housekeeping enhancers (hkCP) and developmental enhancers (dCP). We hypothesized that the two enhancer classes are occupied by distinct architectural proteins, affecting their enhancer–promoter contacts. By evaluating ChIP-seq occupan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

22
236
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 145 publications
(258 citation statements)
references
References 71 publications
22
236
0
Order By: Relevance
“…Visualization of these domains in Drosophila also requires heatmaps at a smaller genomic scale than in humans due to their differences in size (Figure 2AB). Similar to CTCF loops found in human cells, we also found 458 interaction peaks in Drosophila enriched in various architectural proteins, but unlike in humans, we did not see an enrichment of CTCF at the anchors of these loops (Cubeñas-Potts et al, 2016; Rao et al, 2014). Importantly, these interaction peaks do not occur at domain corners (Figure S2A).…”
Section: Resultssupporting
confidence: 77%
See 2 more Smart Citations
“…Visualization of these domains in Drosophila also requires heatmaps at a smaller genomic scale than in humans due to their differences in size (Figure 2AB). Similar to CTCF loops found in human cells, we also found 458 interaction peaks in Drosophila enriched in various architectural proteins, but unlike in humans, we did not see an enrichment of CTCF at the anchors of these loops (Cubeñas-Potts et al, 2016; Rao et al, 2014). Importantly, these interaction peaks do not occur at domain corners (Figure S2A).…”
Section: Resultssupporting
confidence: 77%
“…To gain further insights into the principles controlling the establishment of 3D chromatin organization in D. melanogaster , we combined Hi-C datasets acquired in Kc167 cells to obtain nearly a billion uniquely mapped reads (Cubeñas-Potts et al, 2016). In comparison to the ultra-high resolution Hi-C dataset in humans (Rao et al, 2014), this is equivalent to 12-fold higher contacts at short distances (<10kb) (Figure S1A).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Patterns of genome folding have been scrutinized with ever-increasing precision, but the identity and roles of the underlying molecular actors are still poorly understood, limiting our functional understanding of chromosome architecture. While genome organization and molecular actors differ between distant species (Cubeñas-Potts et al, 2016; Dekker and Heard, 2015; Ea et al, 2015), here we focus on mammals.…”
Section: Introductionmentioning
confidence: 99%
“…In Drosophila , where enhancers have been identified genome-wide, gene expression correlates well with promoter—enhancer contacts [60]. In human cells, Capture Hi-C also found that promoters of active genes participate in chromatin interactions more than inactive genes [61].…”
Section: Discussionmentioning
confidence: 99%